Adsorption of Trimethyltin,Arsenic(V),Zinc and Copper by Palm Oil Mill Sludge Biochar Prepared by Microwave - Ng, Klinsmann Weng Sum (2016)
The increase of palm oil production in Malaysia has led to tremendously large amount of waste generation in the form of liquid and solid annually. Palm oil mill sludge (POMS) is one of the recalcitrant wastes produced from palm oil mill that commonly being either used as palm oil plantation fertiliser or illegally disposed due to its abundance. In order to resolve this problem, reutilisation of POMS to other value added product is encouraged. In this work, POMS was turned into biochar and the product was proposed to adsorb pollutants from wastewater. POMS biochar was produced by using microwave heating. Biochar was prepared by varying the microwave power (W) and holding time (min). The ranges of parameters were as 100 W-500 W and 5 min-25 min for microwave power and holding time respectively. The biochars were tested with the following parameters i.e. trimethyltin (TMT), arsenate (As (V)), zinc (Zn) and copper (Cu). The results determined had shown that POMS biochar are able to adsorb Zn and Cu by the functional groups that are present on the biochar. However there is little or no adsorption of TMT and As (V) onto the biochar. Moreover, it was found that the removal efficiency of Zn and Cu was almost similar at different microwave power and holding time. This could be due to POMS nature. POMS could be a poor dielectric absorber which resulted in a less development of pore on the POMS biochar and alteration of functional group. This was proven by FTIR study. Hence, it can be concluded that the adsorption of Zn and Cu are adsorbed predominantly by the functional groups on POMS biochar. As for TMT and As (V), they do not show effective adsorption due to their anionic in nature which requires modified biochar for effective removal. Thus, it can be concluded that with the microwave frequency used which is 2.45GHz and under dried condition may not be suitable for pyrolysing POMS to biochar using microwave. It is suggested to determine the dielectric properties of POMS before undergo microwave pyrolysis.